This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The given expression is
S = 2 a 3 + 1 a + 2 b 3 + 1 b + 2 c 3 + 1 c =
2 a 3 + 1 a + 2 b 3 + 1 b + a 3 b 3 + 2 a 2 b 2
(since a b c = 1 ).
This attains a maximum when
∂ a ∂ S = 0 , ∂ b ∂ S = 0 .
Differenting and doing some mathematics, this yields a − b = 0 ⟹ a = b . The maximum value of the expression is
2 a 3 + 1 2 a + a 6 + 2 a 4 .
This will be maximum when it's rate of change goes zero, that is
( 2 a 3 + 1 ) 2 2 − 8 a 3 + ( a 6 + 2 ) 2 8 a 3 − 2 a 9 = 0 ⟹ a = 1 ⟹ b = a = 1 .
The maximum value is now
S m a x = 2 × 1 3 + 1 2 + 1 6 + 2 1 4 = 3 2 + 3 1 = 1 .